ENVIRONMENTAL KNOWLEDGE AND LITERACY: DOES IT INFLUENCE ENVIRONMENTAL AWARENESS? - Faizah, Ana Nur; Amin, Saiful; Bashith, Abdul; Kurniawan, Muchammad Akbar; Mkumbachi, Ramadhani Lausi (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Education has an important role in fostering a self-conscious attitude towards the environment. Social science students as prospective teachers who teach the environment in their curriculum are required to have high environmental knowledge and literacy. It is assumed that this can increase environmental awareness for them. This study aims to 1) determine the effect of environmental knowledge on environmental awareness. 2) Knowing the effect of environmental literacy on environmental awareness. 3) Know the effect of environmental knowledge and literacy on environmental awareness. This quantitative research uses a correlational type. The population in this study were students of the Social Science Education Department, UIN Maulana Malik Ibrahim Malang who were taking the Physical Geography course on the Sub-theme of the Environment and its Conservation with a total of 118 people. The sample taken was 91 people based on the Slovin’s formula. The instrument was a questionnaire to measure environmental literacy and awareness, and a test to measure the level of environmental knowledge. The research data were analysed with multiple linear regression. The results showed that 1) environmental literacy affects environmental awareness. 2) Environmental knowledge has no effect on environmental awareness. 3) Environmental literacy and knowledge together affect environmental awareness.